An investigation into the drug disposition of the spleen organ as a potential immuno-therapeutic target - Inuwa, Patience G. (2024)
The development of new therapeutic strategies or treatment options occur, most often, to meet a demand or a need not yet encountered. For the treatment of many diseases, conventional approaches using drugs as therapeutic agents were directed specifically at the indication or in combination with radiotherapy to treat the presumed condition(s). However, severe adverse side effects resulting from these approaches made researchers even more diligent and resilient in striving for solutions to the disease phenomenon. In recent years, immunotherapy has become the emerging new generation strategy to transform the treatment of cancer by using a patients’ own immune system to kill cancerous cells. This has since been met with a lot of challenges especially when tumour cells develop the ability to evade the host immune system or where a breakthrough has been made, the success is only apparent on certain types of cancer. The concept of immunotherapy was powerful enough, but it required the right execution; as with cancer, this solution brought many more unanswered questions. Nonetheless, the revelation and acknowledgment that the immune system is not only fundamental but capable in treating any disease or illness, is a significant step towards changing the direction of how therapeutic strategies are designed. If the immune system is considered as this big switch that can be turned on and off, then research should be focussed on what regulates the immune system. The spleen as a major regulator of the immune system expression, in combination with being a host to a population of immune cells, has catapulted the organ to attention within the clinical scientific community. Stimulating an immune response is the basis of immunotherapy, in which the spleen can be used to demonstrate just that. Moreover, the clinical significance of drug kinetics and its effects in the liver has shown that drug research in the spleen is limited since interest in the liver is driven by the knowledge as the main site of hepatic drug metabolism. Yet the spleen has potential in establishing itself as a possible therapeutic target even though current research in the spleen has shown no indication that it can metabolise drugs. To prove the notion that the spleen can process therapeutic drugs and with the use of precision drugs aimed to specifically cause the activation of immune cells that then generates an immense immune response will be a significant event. Therefore, this study aims to examine the drug disposition in the spleen by discovering its drug metabolising features and understanding its interactions with drugs. This will involve investigating the enzymes responsible for breaking down drugs in the body, but it would also be an indicator of the spleen’s drug uptake qualities; another confirmation that drug transporters might be at play here and providing insight into the distribution of drugs within the spleen. Cytochrome P450 (CYP450s) and (UDP)-glucuronosyltransferase (UGTs) are known as major contributors to drug metabolism of clinically used drugs, and their activities were investigated to represent phase I and II reactions respectively. The following experimental procedures presented in this study were set to evaluate the expression of these enzymes at genetic, protein and functional level in rat and pig spleens which resulted in delivering some promising data. Hence, the work portrayed here is novel in determining the drug disposition process in the spleen. In addition, the therapeutic drug substrates known for their major CYP450 or UGT probes were evaluated to monitor the enzyme kinetics in the spleen, and the observations resulting from the metabolite formation profiles in pig spleen suggests that the spleen is capable of metabolising drugs. Consequently, further investigation in assessing the mechanisms of metabolic enzymes, the identification of the spleen’s major CYP450s or UGTs associated to drug metabolism, and extensive kinetic analysis quantitating these enzymes activities are all required to solidify the spleen’s status as a potential immunotherapeutic target.